Medieval religion : new approaches - Berman, Constance H. (Rewriting histories., 2005)
Constance Hoffman Berman presents an indispensable collection of the most influential and revisionist work to be done on religion in the Middle Ages in the last two decades. Bringing together an authoritative list of scholars from around the world, this book is a comprehensive compilation of the most important work in this field. Medieval Religion provides a valuable service for all those who study the Middle Ages, church history or religion.